CHAMPIONING AND PRESERVING ORAL TRADITIONS HERITAGE FOR NATION’S FUTURE GENERATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, July 2016 – The current wave of modernisation which is focusing more on new media has resulted in many oral traditions once championed, now being forgotten and overwhelmed by the wave of globalisation.